Construcción y validación de una prueba de procesamiento elaborativo de la información y de habilidades composicionales como alternativa sustitutoria de la subprueba de la aptitud verbal en los exámenes de admisión a la universidad - Miljánovich Castilla, Manuel (2001)
The central topic of the investigation is the construction and validation of content of a test of prosecution elaborative of the information, of court cognitive, with an eye toward being used in the admission exams to the university and in other similar situations. The prosecution elaborative of the information supposes the abilities of understanding, organization and reorganization of contents, to the service of the optimization of the processes code cognitive, storage and recovery of the information. Such abilities and processes understand, in turn, the abilities specify of classification, analysis-synthesis, comparison, contrasting, of discernment of levels of generality and of causal and chronological sequences, logical reasoning and argumentative capacity The hypothesis of underlying Work in this study sustains that the abilities that it measures the test in reference are more direct and closely related with the academic work of the university' studies that the abilities measured by the verbal subtest of academic aptitude and that, in consequence, its validity predictive of the success in the university studies of any career is bigger than that of this last one. The empiric confirmation of the validity predictive of the Test of Prosecution E1aborativo of the Information is basically matter of another project of investigation, consistent, in a longitudinal study or of pursuit of a sample of students of different careers during the period of its professional formation.